The Power of Modern Technologies in the Fiction of Don Delillo - Martina Pavlikova (Communications - Scientific letters of the University of Zilina, 2018)
This paper analyses the literary work of an American writer Don DeLillo, who belongs among contemporary American writers. He focuses on the manner in which contemporary human consciousness has been shaped being influenced by consumer and military technologies, media and daily life of information. Modern consumer technologies have a strong impact on men. In DeLillo's fictions, modern technologies are not just simple objects in everyday life of his characters. They are able to shape the consciousness of each human. Telephones, nuclear bombs, computers, television sets and modern appliances present a psychological phenomenon which provides the possibilities for actions, what more, it influences the perception of each human being. In his literary work, Don DeLillo discovers the interaction between human characters and their technological environment. DeLillo's characters find expression through the material forms of the technologies they fetishize, but these material forms simultaneously capture and limit the nature of the kind of transcendence they are able to offer. Technology appears to DeLillo's characters as a kind of human dream, which in turn, influences the kind of dreams and desires they have, and thus also the ones they realize in a technological form. They exist in an interaction between technology and self-definition or self-deception. The diversity of modes that is illustrated in DeLillo’s fictions is supplemented by the technologically mediated confluence of his characters and the field of cultural objects in which they appear.